Vegetation complexity and pool size predict species richness of forest birds - Remeš, Vladimír; Harmáčková, Lenka; Matysioková, Beata; Rubáčová, Lucia; Remešová, Eva (Frontiers in Ecology and Evolution, 2022)
Disentangling regional and local drivers of species richness in communities is a long-term focus of ecology. Regional species pools affect local communities by providing their constituent species. Additionally, the amount and variety of resources enhance diversity locally. Here, we investigated whether the same ecological factor (vegetation complexity) shapes both regional and local species richness and thus drives local diversity both indirectly (via pool size) and directly (via facilitating the coexistence of species). We studied passerine birds of woodlands and forests in eastern Australia. We quantified regional species pool size and sampled local bird communities at 63 transects spanning 3000 km. We estimated canopy height both regionally using satellite imagery and locally using vegetation sampling in the field. We studied how species pool size changed with regional canopy height and water availability, and how local species richness changed with pool size and local canopy height. Local species richness increased with both local canopy height and the size of the regional species pool. Pool size, in turn, increased with regional canopy height, which itself increased with water availability. Moreover, local species richness expressed as a proportion of the regional pool also increased with local canopy height. In sum, vegetation complexity indexed by canopy height had a doubly positive effect on local species richness: indirectly by promoting a large regional species pool and directly by facilitating the coexistence of disproportionately many species locally. Regional pools were larger in tall forests probably due to the legacy of extensive moist forests that once covered most of Australia, thus providing a sizeable potential for speciation, diversification, and species persistence. Local species richness was greater in tall, more productive forests with more vegetation layers likely due to more and varied resources (i.e., more potential niches), allowing the coexistence of more individuals and species of consumers.